Application of Changing Fi'il Madhi and Fi'il Mudhori to Fi'il Amr in Arabic Sentences - Juni Fadillah (El-Ma'wa: Journal of Arabic, Translation and Linguistic, 2025)
The term kalimah - Arabic, in Indonesian is called a word, is defined as a collection of several hijaiyyah letters that have meaning, or the smallest unit of utterance that has meaning. All spoken or written sounds, whether consisting of several letters or only one letter that has a concept of meaning, are categorized as kalimah (Indonesian words). This research aims to determine the application of changing Fi'il Madhi and Fi'il Mudhori to Fi'il Amr in Arabic sentences. The method in this research uses a qualitative approach with library research data collection techniques. The results of this research are that fi'il amr is a fi'il that contains the work desired by the mutakallim (speaker) as the person giving the order to be carried out by the mukhattab (interlocutor) as the person being ordered. Its use adjusts to the person you are talking to, and also to whom and how many people you are talking to according to the mukhattab (interlocutor). Fi'il amr also adapts to the wazan of fi'il madhi. The formation of fi'il amr adapts to fi'il madhi and mudhori.